Effect of vitamin C supplementation on the survival rate and histopathological changes of gills and kidneys of tilapia (Oreochromis niloticus) infected by Aeromonas hydrophylla - Dewa Ayu Angga Pebriani; I Ketut Wija Negara; Ni Putu Putri Wijayanti; Sudaryatma, Putu Eka; Putu Angga Wiradana (Journal of Aquaculture and Fish Health, 2024)
This study was conducted to determine the effect of vitamin C supplementation on the survival rate and histopathological changes of gills and kidneys of tilapia infected by Aeromonas hydrophila. Three doses of vitamin C were tested (150; 300; and 450 mg/kg) with two control groups. Tilapia with uniform size (average weight of 14 grams) as the criteria for inclusion were randomly distributed in five ponds with 15 tilapia fish per ponds. Tilapia was fed with hands until full for two weeks. Tilapia was then infected with A. hydrophila to find out the survival rate and histopathological changes of gills and kidneys at the end of the experimental period or 7 days after infection. The supplementation of 150 mg/kg vitamin C in feed increased the survival rate (%) in Tilapia by 86.67% or higher than other treatment and control groups. The damage to gills in terms of lamella separation was found in all treatment groups, as well as kidneys. The results found that the supplementation of 150 mg/kg vitamin C in feed increased survival rate but did not give effective protection on gills and kidneys.